Ability of the coronary angiography-derived index of microcirculatory resistance to predict microvascular obstruction in patients with ST-segment elevation - Wen, Xinyan; Wang, Zhi; Zheng, Bo; Gong, Yanjun; Huo, Yong (Frontiers in Cardiovascular Medicine, 2024)
Background ： The coronary angiography-derived index of microvascular resistance (caIMR) correlates well with the index of microcirculatory resistance (IMR), which predicts microvascular obstruction (MVO). However, the relationship between caIMR and MVO remains unclear.Aim：To evaluate the predictive ability of caIMR of MVO after ST-segment elevation myocardial infarction (STEMI).Methods：CaIMR was calculated using computational flow and pressure simulation in patients with STEMI in whom MVO status had been assessed by cardiac magnetic resonance (CMR) after successful primary percutaneous intervention at Peking University First Hospital between December 2016 and August 2019. The clinical, biochemical, echocardiographic, and CMR characteristics were assessed according to MVO status. The predictive value of the clinical parameters and caIMR was evaluated.Results：Fifty-three eligible patients were divided into an MVO group (n=32) and a no-MVO group (n=21). The caIMR tended to be higher in the MVO group (41.6 U vs 30.1 U; p=0.136). CaIMR and peak cardiac troponin-I (cTNI) were independent predictors of MVO (per 1-U increment in caIMR: odds ratio [OR] 1.044, 95% confidence interval [CI] 1.004-1.086, p=0.030; per 1-ng/l increase in peak cTNI: OR 1.018, 95% CI 1.003-1.033, p=0.022). In receiver-operating characteristic curve analysis, when a cut-off value of 45.17 U was used, caIMR had some ability to predict MVO (area under the curve 0.622, 95% CI 0.478-0.752, p=0.127).Conclusions：CaIMR and peak cTNI were independent predictors of short-term MVO in patients with STEMI who had undergone successful primary percutaneous coronary intervention and may help to identify those at high risk of MVO.